173 The Bidirectional Relationships Between Sleep, Psychological Stress, and Negative Mood in Daily Life among Healthy Latinx Adults. (3rd May 2021) - Alcantara, Carmela; Giorgio, Luciana; Diaz, Sarah; Morris, Melanie; He, Yun; Li, Gen; Schwartz, Joseph; Basner, Robert; Redline, Susan; Davidson, Karina
Abstract: Introduction: While psychological stress is adversely linked to sleep, the bidirectional and temporal relationships between sleep and psychological stress in the context of daily life are largely understudied, particularly among Latinxs. We examined the bidirectional relationships between daily sleep duration, sleep quality, perceived stress, and negative mood in Latinx adults. Methods: Between 2016-2019, healthy Latinxs (N=42), defined as those without any major physical or psychiatric morbidities, and free from polysomnography-assessed sleep disorders, were recruited from a community sample in New York. Participants naïve to study hypotheses completed 40 consecutive days of actigraphy and ecological momentary assessment of psychological stress and negative mood (depressed, anxious mood) using a 0 (not at all) to 10 (extremely) scale, contributing 1713 observations. Daily sleep duration was measured via wrist-actigraphy, and perceived daily sleep quality (1[very bad] to 4[very good]) was assessed via morning self-report. Sources of daily stress, including sociocultural stress, were collected once each evening. Multi-level modeling was used to examine within-person effects and temporal associations with adjustment for day of the week. Results: Mean age=37.2 (SD=11.8), 69.1% women, 36.6% unemployed, 64.3% immigrant, and 38.1% Spanish-speaking. Non-specific stress (43%), work (28%), and family/relationship (21%) stress were the most common sources of daily stress. Discrimination and immigration stress were rarely reported as daily sources of stress (1.2%). Mean nightly sleep duration was 403.9 minutes (±81.3). Preliminary lagged linear mixed models indicated that a 60-minute increase in sleep duration during the night predicted a -.12 change in stress ratings (SE=.001, p<.0001) the next day, as well as -.06 change in anxious mood (SE=.001, p=.003). Better perceived sleep quality on a 4-point scale during the night predicted lower stress ratings (ß=-.11, SE=.05, p=.04) and less anxious mood (ß=-.13, SE=.05, p=.01) the next day. A one-point higher rating of depressed mood during the day predicted a -.03 decrease in perceived sleep quality that night (SE=.01, p<.05). Conclusion: Overall, these results imply distinct associations of sleep with both anxiety and depressed mood. Longer sleep duration and improved perceived sleep quality were associated with subsequent decreased stress and anxiety. Increased depressed mood predicted worse sleep quality that night. Future research should identify the mechanisms of action for these differential associations. Support (if any):